Effect of age and frailty on the efficacy and tolerability of once-weekly selinexor, bortezomib, and dexamethasone in previously treated multiple myeloma - Auner, Holger W; Gavriatopoulou, Maria; Delimpasi, Sosana; Simonova, Maryana; Spicka, Ivan; Pour, Ludek; Dimopoulos, Meletios A; Kriachok, Iryna; Pylypenko, Halyna; Leleu, Xavier; Doronin, Vadim; Usenko, Ganna; et al. (American journal of hematology, 2021)
Elderly and frail patients with multiple myeloma (MM) are more vulnerable to the toxicity of combination therapies, often resulting in treatment modifications and suboptimal outcomes. The phase 3 BOSTON study showed that once-weekly selinexor and bortezomib with low-dose dexamethasone (XVd) improved PFS and ORR compared with standard twice-weekly bortezomib and moderate-dose dexamethasone (Vd) in patients with previously treated MM. This is a retrospective subgroup analysis of the multicenter, prospective, randomized BOSTON trial. Post hoc analyses were performed to compare XVd versus Vd safety and efficacy according to age and frailty status (<65 and ≥65 years, nonfrail and frail). Patients ≥65 years with XVd had higher ORR (OR 1.77, p = .024), ≥VGPR (OR, 1.68, p = .027), PFS (HR 0.55, p = .002), and improved OS (HR 0.63, p = .030), compared with Vd. In frail patients, XVd was associated with a trend towards better PFS (HR 0.69, p = .08) and OS (HR 0.62, p = .062). Significant improvements were also observed in patients <65 (ORR and TTNT) and nonfrail patients (PFS, ORR, ≥VGPR, and TTNT). Patients treated with XVd had a lower incidence of grade ≥ 2 peripheral neuropathy in ≥65 year-old (22% vs. 37%; p = .0060) and frail patients (15% vs. 44%; p = .0002). Grade ≥3 TEAEs were not observed more often in older compared to younger patients, nor in frail compared to nonfrail patients. XVd is safe and effective in patients <65 and ≥65 and in nonfrail and frail patients with previously treated MM.
Keywords: krevní nemoci; dexamethason; Humans; křehkost; lidé středního věku; Hematologic Diseases; multicentrické studie jako téma; Multiple Myeloma; Drug Administration Schedule; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; věkové faktory; senioři; lidé; gastrointestinální nemoci; Triazoles; doba přežití bez progrese choroby; randomizované kontrolované studie jako téma; bortezomib; mnohočetný myelom; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Frailty; stupeň závažnosti nemoci; Male; Middle Aged; Randomized Controlled Trials as Topic; Bortezomib; Retrospective Studies; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Severity of Illness Index; senioři nad 80 let; Progression-Free Survival; retrospektivní studie; triazoly; Age Factors; Kaplan-Meier Estimate; mužské pohlaví; Hydrazines; Clinical Trials, Phase III as Topic; Gastrointestinal Diseases; hydraziny; Multicenter Studies as Topic; rozvrh dávkování léků; klinické zkoušky, fáze III jako téma; Peripheral Nervous System Diseases; nemoci periferního nervového systému